Towards a vision for information technology in civil engineering proceedings of the Fourth Joint International Symposium on Technology in Civil Engineering, November 15-16, 2003, Nashville, Tennessee - Joint International Symposium on Information Technology in Civil Engineering 2003 : Nashville, Tenn.); Flood, Ian; American Society of Civil Engineers. Technical Council on Computer Practices; European Group for Intelligent Computing in Engineering (Reston, VA : American Society of Civil Engineers, 2004)
Details information on the past, present, and future of the information technology advancements in civil engineering. Proceedings cover various aspects among the following topics: successes and failures of information technology, current trends, professional needs for information technology, the future of information technology in Europe and North America, and the design and decision support tools.
Title from opening screen
Includes bibliographical references.
System requirements: Any computer capable of running Adobe Acrobat Reader, version 4.0
Keywords: Civil engineering -- Data processing -- Congresses